Study on Interfacial Crack Initiation of Jointed Rock Mass Based on Interface Fracture Mechanics - Wei Gao; Xin Chen; Chengjie Hu (Fractal and Fractional, 2022)
The fracture of interfacial crack is the main failure type of jointed rock mass. Therefore, it is very important to study the interfacial fracture of jointed rock mass. For the similarity of jointed rock mass and composites (all are composed by two parts, intact materials and their contact interfaces), the interface fracture mechanics widely used for analysis the interface crack of the composites (bimaterials) can be applied to study the interfacial fracture of jointed rock mass. Therefore, based on the basic theories of interface fracture mechanics, the interfacial fracture of jointed rock mass was analyzed, and one new criterion of interfacial crack initiation for jointed rock mass is proposed. Moreover, based on the proposed interfacial crack initiation criterion, the effect of main influence factors on the interfacial crack initiation of jointed rock mass was analyzed comprehensively. At last, by using the triaxial compression numerical tests on a jointed rock mass specimen with interfacial crack, the theoretical studies were verified.